2018
DOI: 10.1038/s41598-018-36141-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeted-pig trial on safety and immunogenicity of serum-derived extracellular vesicles enriched fractions obtained from Porcine Respiratory and Reproductive virus infections

Abstract: The Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) is the etiological agent of one of the most important swine diseases with a significant economic burden worldwide. Unfortunately, available vaccines are partially effective highlighting the need of novel approaches. Previously, antigenic viral proteins were described in serum-derived extracellular vesicles (EVs) from pigs previously infected with PRRSV. Here, a targeted-pig trial was designed to determine the safety and immunogenicity of such extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…One trial reported on extracellular vesicles from virus-infected pigs that were isolated from serum and used as an intramuscular vaccine. 11 The studies on applications of extracellular vesicles discussed in this Account are shown in Table 1.…”
Section: Surface Of Extracellular Vesiclesmentioning
confidence: 99%
“…One trial reported on extracellular vesicles from virus-infected pigs that were isolated from serum and used as an intramuscular vaccine. 11 The studies on applications of extracellular vesicles discussed in this Account are shown in Table 1.…”
Section: Surface Of Extracellular Vesiclesmentioning
confidence: 99%
“…Recent research works have made contributions here by exploring the proteomics of the viral particles and intracellular proteome of this virus [3,63]. Our work was focused on extracellular vesicle-enriched fractions, as these have been shown to be important for several viral infections, and recently they have been used as a vaccination strategy for another important swine disease—PRRS virus [22].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, extracellular vesicles (EVs) have proven to be a promising new vaccination platform for veterinary diseases in situations in which conventional approaches have not been completely successful, such as PRRSV [21,22,23,24]. EVs are small, round vesicles of 50–400 nm in diameter which are secreted by different cell types, and they are classified as microvesicles if formed by the direct budding of the plasma membrane or exosomes if derived from late endosome trafficking and multivesicular body formation before final release to the extracellular space [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Frequencies of IFN‐γ secreting cells were measured as described before [19]. The 96‐well PVDF‐based membrane plates were coated with 15 µg/mL monoclonal antibody overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%